Aprendizaje En Colaboración En Derecho Romano. - María Paula Durán (Revista de Estudios Sociales, 2004)
Collaborative learning is a classroom practice consistent with constructivism which, according to findings from various investigations, enables students to learn the contents of the subject they learn, to handle language proper to such a subject, to develop critical thinking ski l ls, and to generate values such as tolerance and the understanding and respect of the ideas of others, through dialogue with peers in the classroom and under teacher's guidance. Through this investigation I found that collaborative learning helped my Roman Law students from Universidad de los Andes to construct rigorous and precise definitions about this subject's legal concepts throughout the semester. Additionally, I found that my students gained understanding of Roman Law concepts and developed skills to use them in analyzing and resolving complex legal cases through group conversations. Finally, I found that thanks to collaborative learning my students developed social attitudes such as appreciation of learning from others' ideas, and values such as tolerance, respect and solidarity, among others.